The Rise of Influencer Practices Among Psychologists: From Therapy Rooms to Instagram Reels - Burçin Sarı (Social Media + Society)
Professions are neither isolated nor static entities; they operate within a dynamic system that is shaped by the internal and external forces. Today, a novel yet formidable external force is gradually permeating professional domains: influencer creep , driven by neoliberal self-branding rhetoric. This study investigates the diffusion of influencer creep into psychology, a field with strong legal, workplace, and public jurisdiction. Using a multi-method approach, we observed 100 Turkish psychologists’ Instagram practices over 6 months and conducted 20 semi-structured interviews. Findings reveal that Instagram has become an unexpected intermediary in the labor market for psychologists, intensifying to fulfill the three pillars of influencer creep: self-branding, optimization, and authenticity. Psychologists now strategically use the platform as a “visual curriculum vitae,” leveraging its affordances to craft micro-selling points for their self-brand. These efforts also involve negotiating with algorithms, constant optimization efforts, and projecting themselves authentically by trying not to compromise their professional demeanor. Based on these findings, we contend that influencer creep not only alters individual professional practices but also reconfigures the profession itself through four interrelated changes: (a) the expansion of audiences, shifting from small-scale, localized clients to large, mass followings; (b) the redefinition of traditional markers of expertise, where institutional credentials are increasingly replaced by platform-driven metrics; (c) the alteration of traditional gatekeeping structures, as algorithmic systems take on a more prominent role in determining professional recognition and influence; and (d) requiring a new set of skills such as content creation and algorithmic proficiency, often overshadowing conventional professional competencies.